The Relationship between Fast Food and Junk Food Consumption Habits and the Incidence of Anemia Among Students at MAN 1 Makassar - Gama, Arlina Wiyata; Muh. Akhdan Falih Yusuf, (Alami Journal (Alauddin Islamic Medical) Journal, 2025)
Anemia is a condition characterized by a low concentration of red blood cells or hemoglobin (Hb), which is defined as less than 13.5 g/dL in adult men and 11.5 g/dL in adult women. This condition fails to meet the body's physiological needs. This study aims to analyze the relationship between fast/junk food consumption habits and the incidence of anemia among students at MAN 1 Makassar. Quantitative research with a descriptive analytical design and cross-sectional approach was conducted from February to March 2024. A purposive sample of 300 students was used. Primary data were obtained through questionnaires and hemoglobin level measurements using a digital hemoglobin test. These data were then analyzed using the chi-square test. The results showed that most MAN 1 Makassar students consumed fast/junk food infrequently (less than three times per week). Among students who frequently consumed fast/junk food, 89.58% experienced anemia, whereas only 87.56% of those who rarely consumed it did not. The chi-square test revealed a significant difference in anemia incidence between students who rarely consumed fast/junk food and those who frequently did. This study concludes that there is a relationship between dietary consumption habits and the incidence of anemia.